Polymer-supported zinc tetrahalide catalysts for the coupling reactions of CO2 and epoxides - Lee, Bora; Ko, Nan Hee; Ahn, Byoung Sung; Cheong, Minserk; Kim, Hoon Sik; Lee, Je Seung (WILEY-V C H VERLAG GMBH, 2007)
Homogeneous zinc tetrahalide complexes, highly active catalysts for the coupling reactions of alkylene oxide and CO2 produce alkylene carbonates, were heterogenized due to their tendency to decompose produced alkylene carbonates during the distillation process. Heterogenization of homogeneous zinc tetrahalide complexes was achieved by polymerizing 1-alkyl-3-vinylimidazolium zinc tetrahalides. These polymerized zinc tetrahalide catalysts displayed similar activities to their corresponding monomeric analogues for the coupling reactions of carbon dioxide with ethylene oxide (EO) or propylene oxide (PO) to produce ethylene carbonate (EC) or propylene carbonate (PC). TGA studies showed that the polymer-supported zinc tetrahalide catalysts are thermally stable up to 320 degrees C. The catalyst recycle test showed that the supported catalysts could be reused over six times. After removal of the polymer-supported catalyst through a simple filtration, EC was able to be isolated without decomposition.
Keywords: CARBON-DIOXIDE; CYCLIC CARBONATES; EFFICIENT CATALYSTS; ETHYLENE CARBONATE; IONIC LIQUIDS; COMPLEXES; OXIRANES; HALIDE; SYSTEM; OXIDE